Implementation of Centralized Networking System and Integrated Marketing Communication for MSMEs in Buah Batu Bandung - Wulandari, Astri; Suryawardani, Bethani; Marcelino, Dandy; Satrya, Gandeva Bayu; Prawita, Fat’hah Noor; Lukito, Wahyu; Prabawa, Bijaksana (Jurnal Penyuluhan, 2021)
Network security is very important, especially for community service units because a damaged system can affect other systems. Therefore, it is necessary to design and develop a computer network system and security that’s more centralized. Promotional activities are very important to be carried out by every business from the smallest scope to even large companies, because no matter how good the quality of the products the company has, it will not be successful for sale without proper promotion. Referring to the situation and problems faced by partners, our group took the initiative to contribute by providing several alternative solutions whose goals are expected to be useful for partners, by providing training on the implementation of integrated networks and MSME database management, then providing an integrated marketing communication training, workshop on communication marketing tools that can provide a competitive advantage for MSMEs so that MSME marketing tools in Buah Batu District have superior value. With some of the solutions that we offer, the expected final results from this community service activity are network problems and database management can be resolved properly. Furthermore, MSMEs in Buah Batu District have standardized and attractive printed and digital marketing tools.